2020
DOI: 10.3126/ajms.v11i1.26527
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic changes as neuroscience-based cognitive skill training program

Abstract: Background: Brain is an organ that is easily affected by the physical changes.Abnormalities are known to occur with the brain in terms of memory, eyesight, intellect, and balance as the brain is an organ that is easily affected by the physical changes. Executive functions have been shown to be related to academicachievement and the ability to learn, as well as a range of a neurodevelopmental disorders. The failure of many traditional educational interventions for students with specific learning disabilities ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Studies have shown that intervention programs prepared using educational games can be effective in areas where students with difficulties experience problems such as attention and interest and in improving different cognitive functions (Emami Kashfi et al, 2019;Esmaili et al, 2017;García-Redondo et al 2019;). However, the results of the research show that the education of a neurosciencebased computer education program can significantly increase the cognitive performance of students with specific learning disabilities by developing different working memory skills such as speed, memory, attention, flexibility and problem solving (Gray et al, 2012;Sittiprapaporn, 2020). In addition, it is predicted that this development may increase their academic performance.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that intervention programs prepared using educational games can be effective in areas where students with difficulties experience problems such as attention and interest and in improving different cognitive functions (Emami Kashfi et al, 2019;Esmaili et al, 2017;García-Redondo et al 2019;). However, the results of the research show that the education of a neurosciencebased computer education program can significantly increase the cognitive performance of students with specific learning disabilities by developing different working memory skills such as speed, memory, attention, flexibility and problem solving (Gray et al, 2012;Sittiprapaporn, 2020). In addition, it is predicted that this development may increase their academic performance.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Yapılan çalışmalar eğitsel oyunlardan yararlanılarak hazırlanan müdahale programlarının ÖÖG olan öğrencilerin dikkat, ilgi gibi sorun yaşadıkları alanlarda ve farklı bilişsel işlevleri iyileştirmede etkili olabileceğini ortaya koymuştur (Emami-Kashfi ve diğerleri, 2019; Esmaili ve diğerleri, 2017; García-Redondo ve diğerleri, 2019). Bununla birlikte araştırma sonuçları uygulanan bilgisayar eğitimi programının ÖÖG olan öğrencilerin dikkat, esneklik ve problem çözme gibi farklı çalışan bellek becerilerindeki performanslarını önemli ölçüde artırabileceğini göstermektedir (Gray ve diğerleri, 2012;Sittiprapaporn, 2020). Ayrıca ÖÖG olan öğrencilerin çalışan bellek becerilerindeki gelişimin bu öğrencilerin akademik performanslarına olumlu olarak yansıyacağı öngörülmektedir.…”
Section: çAlışmalardaki Katılımcıların Yaşlara Göre Dağılımlarıunclassified
See 1 more Smart Citation